2018
DOI: 10.3389/fsufs.2018.00079
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion-Based Nanostructures for the Delivery of Active Ingredients in Foods

Abstract: This review aims at presenting recent advancements on the design of novel emulsion-based nanostructures for an effective incorporation of active ingredients into foods. The specific characteristics of nanoemulsions, solid lipid nanoparticles, and double emulsions are highlighted. Nanoemulsions are oil-in-water emulsion with droplet sizes below 200 nm that are known to present high stability over time. Moreover, due to their reduced droplet size and therefore maximized active surface area, they are capable of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…These emulsions of curcumin have been found to increase the oral bioavailability of curcumin. Numerous studies have reported on the emulsion‐based delivery systems for curcumin . Bergonzi et al found that a curcumin microemulsion formulation made up of food grade components increased its oral absorption by 70%.…”
Section: Pharmacokinetics/bioavailability Of Curcumin: Problems and Pmentioning
confidence: 99%
See 1 more Smart Citation
“…These emulsions of curcumin have been found to increase the oral bioavailability of curcumin. Numerous studies have reported on the emulsion‐based delivery systems for curcumin . Bergonzi et al found that a curcumin microemulsion formulation made up of food grade components increased its oral absorption by 70%.…”
Section: Pharmacokinetics/bioavailability Of Curcumin: Problems and Pmentioning
confidence: 99%
“…Numerous studies have reported on the emulsion-based delivery systems for curcumin. [149][150][151][152] Bergonzi et al 153 found that a curcumin microemulsion formulation made up of food grade components increased its oral absorption by 70%. In addition, a self-microemulsion formulation of curcumin has been proven to increase the absorption of curcumin by 3.86 times as compared to conventional curcumin suspension when administered orally.…”
Section: Emulsion-based Delivery Systemsmentioning
confidence: 99%
“…In the body, the gastrointestinal tract (GIT) is such that this continuous tube has its own characteristic pH level, containing the acidic stomach and the alkaline intestine (Khutoryanskiy, 2015). Therefore, there is a need for an emulsion-based delivery system specifically designed to control the digestion, release, and absorption of lipophilic components of the GIT (McClements and Li, 2010; Salvia-Trujillo et al., 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Oil-in-water emulsions have gained attention as promising or potential carrier systems to incorporate hydrophobic bioactive compounds such as cyanothiophene inhibitors into aqueous pharmaceutical formulations [ 10 , 11 , 12 , 13 , 14 , 15 ]. The parenteral method is one of the most frequent and effective routes for hydrophobic drug administration.…”
Section: Introductionmentioning
confidence: 99%